Implant comparisons in grazing and finishing spayed heifers - S.B. Laudert; Gerry L. Kuhl; A.J. Edwards (Kansas Agricultural Experiment Station Research Reports, 1987)
Heifers that were flank-spayed plus rumen-ovarian autografted (FS+A) responded similarly to Ralgro®, Synovex-H®, and Synovex-S® implants on' pasture. Grazing heifers spayed by the Kimberling-Rupp technique also responded similarly to Synovex-H and Synovex-S implants. During the finishing phase, heifers implanted with Synovex-S gained 5.7% faster than heifers implanted with Ralgro, and those implanted with Synovex-H were intermediate in performance. There was no statistical interaction between spaying method and implant treatment during either the grazing or finishing phases.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Implant; Heifers; Spayed